Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 5 + 5 ^ 2 + 5 ^ 3 + ... + 5 ^ 50
5 A = 5 ^ 2 + 5 ^ 3 + 5 ^ 4 + ... + 5 ^ 51
5 A - A = ( 5 ^ 2 + 5 ^ 3 + 5 ^ 4 + ... + 5 ^ 51 )
- ( 5 + 5 ^ 2 + 5 ^ 3 + ... + 5 ^ 50 )
4 A = 5 ^ 51 - 5
A = \(\frac{5^{51}-5}{4}\)
A=5^1+5^21+5^3+...+5^50
5^1A=5(5^1+5^2+5^3+..+5^50)
5A=5^2+5^3+..+5^50+5^51
5A-A=(5^2+5^3+..+5^50+5^51)-(5^1+5^2+5^3+..+5^50)
4A=5^51-5^1
A=(5^51-5^1):4
-1997*1996+1/-1995*(-1997)+1996
=-1997*(1995+1)+1/-1*1995*(-1)*1997+1996
=-1997*1995+(-1997)+1/1995*1997+1996
=-1*1997*1995+(-1996)/1995*1997+1996
=-1
1+1/A+1/a2+1/a3+1+.../an+1
=1(1/A/a2/a3/...an)
=1.(1/a1+2+3+...+n)
=1.(1/a6+...+n)
=a6+...+n
1:
I2x+3I = 5
=> 2x+3 = 5 hoặc 2x+3 = -5
=> 2x = 5 - 3 hoặc 2x = -5 - 3
=> 2x = 2 hoặc 2x = -8
=> x = 2 hoặc x = -4
2:
B = 1/2.2/3.3/4.4/5.....27/28
= 1.2.3.4.5.6...27/2.3.4.5.6...28
= 1/28
3:
2A = 2(1+1/2+1/2^2+1/2^3+1/2^4+...+1/2^2015) = 2+1+1/2+1/2^2+1/2^3+...+1/2^2014
=> 2A-A = ( 2+1+1/2+1/2^2+1/2^3+...+1/2^2014)-(1+1/2+1/2^2+1/2^3+...+1/2^2015)
=> A = 2-1/2^2015
MK lm bài 1:
\(\left(a-b\right)\left(a+b\right)=a^2+ab-ab-b^2=a^2-b^2\)
Bài 1:
\(\left(a-b\right)\left(a+b\right)=a^2+ab-ab-b^2\)
\(=a^2-b^2\)
\(-\frac{5}{10}=-\frac{1}{2}\)
\(\frac{18}{33}=\frac{6}{11}\)
\(\frac{19}{57}\)
\(\frac{-36}{-12}=\frac{3}{2}\)